PSIKOEDUKASI SEHAT EMOSI DI TENGAH PANDEMI DI GEREJA STANISLAUS KOSTKA, KRANGGAN, CIBUBUR - Kristiyani, Veronica; Lunanta, Lita Patricia (Universitas Esa Unggul, 2021)
Covid-19 pandemic brought a disruption to society. There were a lot of changing plans in every area or life, starting from home-based learning for the students and problems in the economy. These changes, in one way or another, put people in unrealized griefs. Losses of the life that they know and loss of control of unknown things. This psychoeducation was held online to socialize this condition of society, especially to those who were the member of the church as the location of this occasion. Understanding of the current condition was then continued with the discussion about the emotion regulation process that they could do. Each step was discussed and then ended with a relaxation activity in the form of self reflection. This psychoeducation activity was hoped to be used by participants in facing daily struggle with emotions. Questions and answers session was interactively held throughout the presentation and discussion of materials. Participants gave positive feedback from the pooling taken. They stated that the materials are relevant and showed interest to join similar seminars with further topics about emotions . Keywords—emotion regulation, covid-19, psychoeducation